2014
DOI: 10.1155/2014/986285
|View full text |Cite
|
Sign up to set email alerts
|

Is End-Stage Ankle Arthrosis Best Managed with Total Ankle Replacement or Arthrodesis? A Systematic Review

Abstract: Introduction. End-stage ankle osteoarthritis is a debilitating condition. Traditionally, ankle arthrodesis (AA) has been the surgical intervention of choice but the emergence of total ankle replacement (TAR) has challenged this concept. This systematic review aims to address whether TAR or AA is optimal in terms of functional outcomes. Methods. We conducted a systematic review according to PRISMA checklist using the online databases Medline and EMBASE after January 1, 2005. Participants must be skeletally matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The most recent systematic review by Jordan et al . does not show convincing differences in outcomes for ankle arthrodesis and TAR . The lack of evidence to support the use of TAR in haemophiliacs means that many opt for arthrodesis .…”
Section: Discussionmentioning
confidence: 96%
“…The most recent systematic review by Jordan et al . does not show convincing differences in outcomes for ankle arthrodesis and TAR . The lack of evidence to support the use of TAR in haemophiliacs means that many opt for arthrodesis .…”
Section: Discussionmentioning
confidence: 96%
“…7,8,12 Ankle arthrodesis has been demonstrated to result in significant pain alleviation and good functional results. 9,10,13,14 In recent years there has been a trend towards arthroscopic ankle arthrodesis because it has been shown to result in shorter hospital stay, lower initial complication rate and better early outcome. 15 Performing arthroscopic ankle arthrodesis in cases of severe deformity, however, may be challenging, or impossible.…”
Section: Ankle Osteoarthrosismentioning
confidence: 99%
“…In terms of function and pain alleviation, mid-term results after TAA are equivalent to those following ankle arthrodesis. 9,10,14 In terms of biomechanics, neither the arthrodesis nor the TAA is able to restore normal gait. Nevertheless, TAA is associated with a more physiological gait pattern than arthrodesis.…”
Section: Ankle Osteoarthrosismentioning
confidence: 99%
“…A recent systematic review assessing ankle replacement and ankle fusion in patients with ankle arthrosis of any cause included four comparative studies (three retrospective studies and one prospective non-randomised trial) involving a total of 303 ankles 24. Two studies reported better improvements in functional outcomes with ankle replacement and the other two found no difference between the two procedures.…”
Section: Ankle Replacementmentioning
confidence: 99%